Endophytic Bacteria Consortia as Biocontrol Against Brown Spot Disease (Helminthosporium oryzae) and Growth Promotion in Rice - Eri Sulyanti; Zurai Resti; Haliatur Rahma; Darnetty Darnetty; Ujang Khairul; Nurhaliza Nurhaliza; Silvia Oktaviani (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2025)
The brown spot disease (BSD) caused by Helminthosporium oryzae in rice can lead to yield losses of up to 45 %. Using endophytic bacterial consortia as a biological agent is one of the most potential control methods for resisting the disease. This study aimed to obtain an endophytic bacterial consortium with the best efficacy in controlling BSD and its ability to enhance rice plant growth. Statistical analysis in this study was made using Analysis of Variance (ANOVA) with Duncan’s Multiple Range Test (DMRT) in a randomized experimental design comprising five treatments with five replications. The treatments included: A (Serratia marcescens ULG1E4 + S. marcescens JB1E3), B (S. marcescens ULG1E4 + S. marcescens JB1E3 + Serratia marcescens JB1E2), C (Bacillus sp. SJI + Serratia marcescens ULG1E4), D (positive control), and E (negative control). Testing was conducted in planta, with the introduction of the bacterial consortium (10⁸ cells/mL) via seed and root soaking methods. Subsequently, the leaves of 30-day-old rice plants were inoculated with H. oryzae by spraying a conidial suspension of 10⁶ conidia/ml. Parameters observed included disease progression (incubation period, incidence, and severity), seedling growth metrics (height, leaf number, root length, fresh and dry biomass), and overall plant development (plant height, leaf number, and tiller count). The results demonstrated that the consortium of Serratia marcescens ULG1E4, Serratia marcescens JB1E3, and Serratia marcescens JB1E2 effectively controlled BSD, achieving a 53.69% reduction in disease severity and promoted rice plant growth, evidenced by a 30.63% increase in leaf number